Design and Operation of Heat Exchangers 1992
DOI: 10.1007/978-3-642-84450-8_7
|View full text |Cite
|
Sign up to set email alerts
|

Design Improvements of a Shell and Tube Heat Exchanger Based on Practical Experience and Numerical Analysis

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The characteristics of vortex shedding from tube banks with closely mounted serrated fin was investigated in [1] where the relationship between the Strouhal number defined by the equivalent diameter as the characteristic length of a finned tube in the tube banks and the Strouhal number map for bare-tube banks was examined. Whereas in [2] the author has presented various outlet conditions of a shell and tube heat exchanger theoretically and experimentally in which it is observed that prime parameter geometry of outlet affects the performance, maintenance and life span of a vertical shell and tube evaporator. The heat transfer enhancement has been achieved in [3], by modifying the configuration of a shell-and-tube heat ex-changer, through the installation of sealers in the shellside.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of vortex shedding from tube banks with closely mounted serrated fin was investigated in [1] where the relationship between the Strouhal number defined by the equivalent diameter as the characteristic length of a finned tube in the tube banks and the Strouhal number map for bare-tube banks was examined. Whereas in [2] the author has presented various outlet conditions of a shell and tube heat exchanger theoretically and experimentally in which it is observed that prime parameter geometry of outlet affects the performance, maintenance and life span of a vertical shell and tube evaporator. The heat transfer enhancement has been achieved in [3], by modifying the configuration of a shell-and-tube heat ex-changer, through the installation of sealers in the shellside.…”
Section: Introductionmentioning
confidence: 99%
“…In this proposed work design, development & testing of STHE is carried out. Along with the parameter considered in [1][2][3][4][5][6][7][8], vibration analysis is performed to optimized unsupported span of tube by using HTRI software. Detail overview on work carried out by researchers is presented in Section 1, Section 2 & 3 states mechanics of flow-induced vibration and the current problem definition & objective, details of STHE is given in Section 4.…”
Section: Introductionmentioning
confidence: 99%